Investigations of immunotoxicity and allergic potential induced by topical application of triclosan in mice - Anderson, Stacey E. (J Immunotoxicol, 2015)
Triclosan is an antimicrobial chemical commonly used occupationally and by the general public. Using select immune function assays, the purpose of these studies was to evaluate the immunotoxicity of triclosan following dermal exposure using a murine model. Triclosan was not identified to be a sensitizer in the murine local lymph node assay (LLNA) when tested at concentrations ranging from 0.75–3.0%. Following a 28-day exposure, triclosan produced a significant increase in liver weight at concentrations of ≥ 1.5%. Exposure to the high dose (3.0%) also produced a significant increase in spleen weights and number of platelets. The absolute number of B-cells, T-cells, dendritic cells and NK cells were significantly increased in the skin draining lymph node, but not the spleen. An increase in the frequency of dendritic cells was also observed in the lymph node following exposure to 3.0% triclosan. The IgM antibody response to sheep red blood cells (SRBC) was significantly increased at 0.75% – but not at the higher concentrations – in the spleen and serum. These results demonstrate that dermal exposure to triclosan induces stimulation of the immune system in a murine model and raise concerns about potential human exposure.